2021
DOI: 10.31219/osf.io/7kn9c
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Perspectives and experiences of autistic multilingual adults: A qualitative analysis.

Abstract: Please note this paper is being peer-reviewed for publication in Autism in Adulthood:Nolte, K., Fletcher-Watson, S., Sorace, A., Stanfield, A., & Digard, B.G. (2021). Perspectives and experiences of autistic multilingual adults: A qualitative analysis. (Under revision for Autism in Adulthood)Please do not cite this preprint.Background: The combined experience of autism and bilingualism is poorly understood, leading to poor support and guidance for autistic people in multilingual environments or interes… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…While some autistic bilinguals report learning their second language at school (Digard et al, 2020 ), autistic students can encounter barriers to modern language learning in mainstream education. There is a dearth of research addressing best practices for additional language learning for neurodivergent students, but evidence suggests that autistic pupils are often advised not to study modern foreign languages (Essex and MacAskill, 2020 ), which can penalise them by limiting their education, employment, and leisure opportunities (Nolte et al, 2021 ). This practice stems from a misunderstanding of autistic people's abilities, and a lack of understanding of autism.…”
Section: Educationmentioning
confidence: 99%
See 1 more Smart Citation
“…While some autistic bilinguals report learning their second language at school (Digard et al, 2020 ), autistic students can encounter barriers to modern language learning in mainstream education. There is a dearth of research addressing best practices for additional language learning for neurodivergent students, but evidence suggests that autistic pupils are often advised not to study modern foreign languages (Essex and MacAskill, 2020 ), which can penalise them by limiting their education, employment, and leisure opportunities (Nolte et al, 2021 ). This practice stems from a misunderstanding of autistic people's abilities, and a lack of understanding of autism.…”
Section: Educationmentioning
confidence: 99%
“…Howard et al ( 2019 ) reported that bilingual children living in multilingual environments are more positive about bilingualism than their peers in monolingual settings, especially regarding social and communication opportunities linked with bilingualism. Adults also reported that bilingualism had supported their relationships with family and friends and increased their access to hobbies and educational and employment opportunities (Nolte et al, 2021 ). Importantly, bilingualism had given them feelings of increased self-efficacy, self-confidence and assurance in social interactions and had helped them to better understand themselves and others.…”
Section: Introductionmentioning
confidence: 99%
“…While some autistic bilinguals report learning their second language at school (Digard et al, 2020), autistic students can encounter barriers to modern language learning in mainstream education. There is a dearth of research addressing best practices for additional language learning for neurodivergent students, but evidence suggests that autistic pupils are often advised not to study modern foreign languages (Essex & MacAskill, 2020), which can penalise them by limiting their education, employment, and leisure opportunities (Nolte et al, 2021). This practice stems from a misunderstanding of autistic people's abilities, and a lack of understanding of autism.…”
Section: Educational Barriersmentioning
confidence: 99%
“…Howard et al (2019) reported that children living in multilingual environments are more positive about being bilingual than those in monolingual settings in regard to social and communication opportunities. Adults also reported that bilingualism had supported their relationships with family and friends and increased their access to hobbies and educational and employment opportunities (Nolte et al, 2021). Importantly, bilingualism had given them a feeling of increased self-efficacy, self-confidence and assurance in social interactions and had helped them to better understand themselves and others.…”
Section: Introductionmentioning
confidence: 99%
“…Reports from adults reinforce and extend this position, by showcasing the positive ways in which speaking multiple languages can impact quality of life. For example, qualitative data from bilingual and multi-lingual adults have shown that bilingualism had facilitated their access to interests and hobbies, as well as employment opportunities (Nolte et al, 2021). Bilingualism also broadened participants’ mind-sets and contributed to increased self-confidence in social interactions (Digard et al, 2022).…”
mentioning
confidence: 99%